Coffee and Caffeine Consumption for Human Health - Del Coso, Juan (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The year 2019 has been prolific in terms of new evidence regarding the effects of coffee and caffeine consumption on diverse aspects of human functioning. This book collects 20 high-quality manuscripts published in Nutrients that include original investigation or systematic review studies of the effects of caffeine intake on human performance and health. The diversity of the articles published in this Special Issue highlights the extent of the effects of coffee and caffeine on human functioning, while underpinning the positive nature of most of these effects. This book will help with understanding why the natural sources of caffeine are so widely present in the nutrition behaviors of modern society.